2017
DOI: 10.1039/c7dt02927f
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of a perovskite-type metal–organic framework crystal

Abstract: We report for the first time the investigation of thermal conductivity for a perovskite-type MOF crystal. In situ single crystal X-ray diffraction technology was employed to track the phase transition of a newly synthesized perovskite MOF. The perovskite MOF crystal exhibits a low thermal conductivity of 1.3 W (K m) in comparison to most of the bulk crystal materials at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…For the pristine HKUST-1 case (i.e., no adsorbates), measured thermal conductivities ranged between 0.44 and 0.73 W m −1 K −1 across all thin film samples, with the single crystals at the higher end of that range at 0.69 ± 0.05 W m −1 K −1 . These values are in the typical range of other room temperature MOF thermal conductivity measurements, such as IRMOF-1 (0.32 W m −1 K −1 ) 16 , ZIF-8 (0.32 W m −1 K −1 ) 21 , and perovskite-like MOF-1 (1.3 W m −1 K −1 ) 18 . Our single crystal value for HKUST-1 is higher than previously reported by Chae et al (0.26 W m −1 K −1 ) 22 .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…For the pristine HKUST-1 case (i.e., no adsorbates), measured thermal conductivities ranged between 0.44 and 0.73 W m −1 K −1 across all thin film samples, with the single crystals at the higher end of that range at 0.69 ± 0.05 W m −1 K −1 . These values are in the typical range of other room temperature MOF thermal conductivity measurements, such as IRMOF-1 (0.32 W m −1 K −1 ) 16 , ZIF-8 (0.32 W m −1 K −1 ) 21 , and perovskite-like MOF-1 (1.3 W m −1 K −1 ) 18 . Our single crystal value for HKUST-1 is higher than previously reported by Chae et al (0.26 W m −1 K −1 ) 22 .…”
Section: Resultssupporting
confidence: 68%
“…Relative to gas adsorption, however, little is understood about how to tune thermal conductivity in MOFs. Broadly, MOFs are thermal insulators, with thermal conductivities typically <2 W m −1 K −1 at room-temperature 16 18 . Moreover, it has been an open question as to how adsorbates influence MOF thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Gunatilleke et al have reported a perovskite-type MOF with a thermal conductivity of 1.30 W m −1 K −1 at room temperature. [179] Doping MOFs with materials of high thermal conductivity is a promising and effective approach to enhance the thermal conductivity of MOFs. MOF-5 composites doped with 10 wt% of expanded natural graphite show a significant enhancement (≈460%) of the thermal conductivity.…”
Section: Thermal Conductivity Of Adsorbentsmentioning
confidence: 99%
“…The thermal conductivity of bulk crystals is even lower. Gunatilleke et al have reported a perovskite‐type MOF with a thermal conductivity of 1.30 W m −1 K −1 at room temperature . Doping MOFs with materials of high thermal conductivity is a promising and effective approach to enhance the thermal conductivity of MOFs.…”
Section: Mofs In Co2 Capture Practicementioning
confidence: 99%
“…In spite of the fact that MOFs possess many unique properties, the thermal conductivity of MOFs is usually extremely low, which is typically smaller than 2 Wm −1 K −1 at room temperature, [19][20][21] due to their ultra-porous structure 22 and weak coordination bond. 23 The property of extralow thermal conductivity is considered as the bottleneck of MOFs in energyrelated applications such as adsorbent-based fuel tanks for methane or hydrogen-powered vehicles.…”
Section: Introductionmentioning
confidence: 99%